Hex - Olde Heuvelt, Thomas, 1983- (Tor, 2016)
"Welcome to Black Spring, the seemingly picturesque Hudson Valley town haunted by the Black Rock Witch, a seventeenth-century woman whose eyes and mouth are sewn shut. Muzzled, she walks the streets and enters homes at will. She stands next to children's beds for nights on end. Everybody knows that her eyes may never be opened or the consequences will be too terrible to bear. The elders of Black Spring have virtually quarantined the town by using high-tech surveillance to prevent their curse from spreading. Frustrated by being kept in lockdown, the town's teenagers, decide to break their strict regulations and go viral with the haunting. But, in so doing, they send the town spiraling into dark, medieval practices of the distant past."--Jacket.